Internship Management Information System at Batik TV Pekalongan - Giarto, Debora Octavia; Nugroho, Agus Cahyo; Harnadi, Bernardinus (Journal of Business and Technology, 2023)
Batik TV Pekalongan City as a government agency provides opportunities for students and college students to do internships. Batik TV does not yet have an internship information system so that internship management is still manual and not computerized. This makes it less efficient and time-consuming because interns must meet the supervisor every day to report daily activities. The purpose of this research is to create an Information System for Managing Internship Activities at Batik TV Pekalongan to make it easier to manage internship activities. This system uses a prototype development method including listen to customer, build/revise mock up, customer test drives mock up. The result of this research is the establishment of an Internship Management Information System that makes it easier for interns to write daily internship activities, makes it easier for supervisors to check daily activity reports, and makes it easier for admins to manage internship data.